A Role for the Action Observation Network in Apraxia After Stroke - Pizzamiglio, Gloria; Zhang, Zuo; Kolasinski, James; Riddoch, Jane M.; Passingham, Richard E.; Mantini, Dante; Rounis, Elisabeth (Frontiers in Human Neuroscience, 2019)
Limb apraxia is a syndrome often observed after stroke which affects the ability to perform skillful actions, despite intact elementary motor and sensory systems. In a large cohort of unselected, stroke patients with lesions to the left, right and bilateral hemispheres, we used voxel-based lesion symptom mapping (VLSM) on clinical CT head images to identify the neuroanatomical correlates of the impairment on three tasks investigating praxis skills in patient populations. These included a meaningless gesture imitation task, a gesture production task involving pantomime of transitive and intransitive gestures, and a gesture recognition task involving recognition of these same categories of gestures. Neocortical lesions associated with poor performance on these tasks were all in the left hemisphere. They involved pre-striate and medial temporal cortices, the superior temporal sulcus, inferior parietal area PGi, the superior longitudinal fasciculus underlying the primary motor cortex and the uncinate fasciculus, subserving connections between temporal and frontal regions. No significant lesions were identified when language deficits, using a picture naming task, were controlled for. The implication of superior temporal sulcus and anatomically connected prestriate and inferior parietal regions challenges traditional models of the disorder. The network identified has been implicated in studies of action observation, which might share cognitive functions sub-serving praxis and language skills.